2009
DOI: 10.1177/1049732309350686
|View full text |Cite
|
Sign up to set email alerts
|

African American Women’s Beliefs, Coping Behaviors, and Barriers to Seeking Mental Health Services

Abstract: Little is known about African American women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 45 publications
3
114
0
Order By: Relevance
“…Ward and colleagues (Ward, Clark, & Heidrich, 2009) explored beliefs about health and illness among 15 Black women in the Midwest. These women not only endorsed well-established causes of mental illness such as genetics, trauma, and environment, but also highlighted culturally related factors including the "daily stress and hassles" of being Black, racism, discrimination, dual discrimination (gender and race), oppression, and injustice.…”
Section: Racialized Identitymentioning
confidence: 98%
“…Ward and colleagues (Ward, Clark, & Heidrich, 2009) explored beliefs about health and illness among 15 Black women in the Midwest. These women not only endorsed well-established causes of mental illness such as genetics, trauma, and environment, but also highlighted culturally related factors including the "daily stress and hassles" of being Black, racism, discrimination, dual discrimination (gender and race), oppression, and injustice.…”
Section: Racialized Identitymentioning
confidence: 98%
“…By using a realist approach for the evidence British Journal of General Practice, December 2015 e818 • Social (dis)approval 31,73 • Perceived discrimination 32,73,86 One review suggested that face-to-face consultations were essential for communication about emotional states. 87 Other evidence suggests that patients do communicate their emotional states with GPs via email, 88 and are able to discuss embarrassing or sensitive questions 89 Patients consulting for physical problems can feel less intimidated via video link and able to ask more questions 90 One review found that teenage girls willingly emailed a health professional in a magazine column to discuss problems/queries that they would not necessarily talk about face to face 91 Online disinhibition theory suggests people express themselves more openly, disclose more, and say things in cyberspace that they would not face to face 88 The removal of the patient 'being seen' seeking help potentially removes the embarrassment, social disapproval, and stigma that some patients may experience at healthcare centres 68,93 Digital clinical communication will reduce patients' inhibition and sense of intimidation and promote patient disclosure and asking of questions review, evidence was drawn from many disciplines to answer a research question for general practice, at a time when little good-quality evidence exists, and before the UK NHS has systems in place to support digital communication between clinician and patient.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Historically and currently, African American women tend to underutilize mental health services, relative to other groups [32,33]. A recent study with a sample of 3,570 (56% of the sample were female) showed that only 26.1% of African Americans with MDD used specialty mental health care within a 12-month period.…”
Section: Mental Health Service Use and Quality Of Carementioning
confidence: 99%
“…Similarly, although more recent literature documents African Americans tendency to rely on spirituality and religious coping to address mental health needs, none of the studies examined effectiveness of psychotherapy incorporating religion/spirituality in reducing symptoms of MDD. Given that within the African American community, women, the elderly and those facing health problems are more likely to tap into religion/spirituality as a coping mechanism [33,55], efficacy research examining health outcomes associated with use of psychotherapy integrated with religion/spirituality are critically needed. Such research has the potential to increase delivery of culturally sensitive patient-centered care to African American women.…”
Section: African American Women and Use Of Religious/spiritual Copingmentioning
confidence: 99%
See 1 more Smart Citation